Remaking of African traditional religions under the influence of modernity - Onwurah, Emeka (Journal of Dharma, 1987)
It is hard to imagine the scope and rapidity of change that has takenplace throughout the African continent in the last one century or so. Changesthat have evolved gradually in Western Europe and America over many years have taken place in many parts of Africa at alarming speed. Changes that gradually came about by way of response to changing conditions and evolving perspectives have been forced upon African culture with little psychological or physical preparation. This change and its rapidity is in large measure due to the influence, welcome or otherwise, of western culture on Africa. The fusion and symbiosis of traditional African culture and Western Euro-American culture has not proved to be either an easy or a desirable fusion. Many problems have arisen and many areas of socalled "progress" have viewed as a highly questionable force for good.
free
Keywords: Africa.; Christianity and African religions; Culture and religion; Economic development; Indigenization of worship